SAE Technical Paper Series 1998
DOI: 10.4271/981665
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the International Space Station System-Level Trace Contaminant Injection Test

Abstract: Trace contaminant control onboard the International Space Station will be accomplished not only by the Trace Contaminant Control Subassembly but also by other Environmental Control and Life Support System subassemblies. These additional removal routes include absorption by humidity condensate in the Temperature and Humidity Control Condensing Heat Exchanger and adsorption by the Carbon Dioxide Removal Assembly. The Trace Contaminant Injection Test, which was performed at NASA's Marshall Space Flight Center, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Such trace contaminant removal functional assist has been observed and characterized previously. [10][11] Evaluation of the TCCS performance determined a mean effective overall 88% contaminant removal efficiency. As displayed by Fig.…”
Section: Trace Contaminant Control Performancementioning
confidence: 99%
“…Such trace contaminant removal functional assist has been observed and characterized previously. [10][11] Evaluation of the TCCS performance determined a mean effective overall 88% contaminant removal efficiency. As displayed by Fig.…”
Section: Trace Contaminant Control Performancementioning
confidence: 99%
“…System level testing has shown that CDRA was effective in the removal of acetone at 33% efficiency, methylene chloride at 50%, methanol at 33% efficiency, m-xylene at 53% efficiency, and ammonia at 43% efficiency. [8] …”
Section: Trace Contaminant Controlmentioning
confidence: 99%
“…The Environmental Control and Life Support System (ECLSS) for the ISS has a Trace Contaminant Control Subassembly (TCCS) that is used to absorb or decompose trace amounts of contaminants in the cabin atmosphere that could otherwise gradually build up over time to toxic levels. The TCCS consists of an activated carbon bed that absorbs the longer chain carbon molecules, a catalytic converter to thermally decompose contaminants, and a lithium hydroxide bed to neutralize the acidic byproducts of the decomposition reaction 3 . The thermal decomposition reaction occurs at temperatures of 450ºC.…”
mentioning
confidence: 99%